A Basic Canonical Form of Discrete-Time Compartmental Systems - Bru, R.; Canto, R.; Ricarte, B.; Rumchev, Ventseslav (Hikari Ltd, 2007)
The transfer functions of discrete-time SISO compartmental systems whose compartments are connected either in series or in parallel are characterized, and then the corresponding realization problem is studied. The obtained results are extended to the transfer matrix of N periodic compartmental systems.